THE ROLE OF SOCIAL SUPPORT IN ADDRESSING EMPLOYMENT AND ENTREPRENEURSHIP CHALLENGES: STRATEGIES FOR BUILDING A SUSTAINABLE LOCAL ECONOMIC ECOSYSTEM IN MANDALIKA - Malik, Adam; edy, Nur; Rahman, Abdul; Haryanti, Tuti; Latifah, Ayi; Krisnamurti, Reza Mahendra (Universitas Tadulako, 2024)
Mandalika, recognized as one of Indonesia's super-priority tourism attractions, offers substantial prospects for local economic advancement. Nonetheless, obstacles in employment and entrepreneurship endure due to skill discrepancies, restricted access to resources, and inadequate social support systems. This study assess: (i) ascertain the function of social support in mitigating employment and entrepreneurial obstacles and (ii) investigate solutions for creating a sustainable local economic ecosystem. Data were obtained utilizing a mixed-method approach, encompassing surveys, in-depth interviews, focus group discussions, and document analysis. The results demonstrate that social support is essential in alleviating employment obstacles, especially in enhancing access to training, mentorship, and financial resources. The study underscores a deficiency in stakeholder integration, as local governments, business organizations, and university institutions exhibit insufficient coordination in promoting sustainable entrepreneurship. The study delineates primary obstacles, such as the lack of organized business models, insufficient marketing acumen, and poor financial oversight inside micro and small firms. The report offers a multi-stakeholder entrepreneurship strategy that focuses on accessibility, capacity building, and ongoing mentorship to address these concerns. These initiatives, along with enhanced policy frameworks and digital adaption, are crucial for promoting economic resilience. The findings highlight the necessity for a holistic support framework that amalgamates community involvement, regulatory modifications, and sustainable business methodologies to guarantee equitable economic advancement in Mandalika. Future study should concentrate on assessing the enduring effects of social support systems on improving economic sustainability and resilience.